Development of a drug delivery system using cockle shell-derived aragonite nanoparticles to treat osteosarcoma in a rat model - Fu, Wenliang (2017)
Osteosarcoma (OS) is a highly malignant primary bone cancer and most prevalent in children and young adults. The improvement in patient survival outcome has been stagnation,the 5-year survival rate for patients with metastasis OS is less than 20%. Chemotherapy is associated with severe side effects due to nonspecific tissue biodistribution. The development of multidrug resistance is another obstacle faced with chemotherapy for OS. Biogenic calcium carbonate (CaCO3) nanoparticles show unique advantages and the potential as delivery system. However, their anticancer efficacy and safe dosage have not been tentatively studied, especially in vivostudy. The general objective of this research is to investigate the effectiveness of cockle shells-derived CaCO3 aragonite nanoparticles (ANPs) as a pH sensitive drug vehicle in themanagement of OS.In the first part of the study, ANPs were prepared and loaded with doxorubicin (DOX). The morphology and compositions of the nanoparticles were characterized. The results demonstrated ANPs were spherical-shaped pure aragonite particles, with a distributed size of 20-60 nm in diameter and -46.17 ± 3.82 mV zeta potential.The drug loading study demonstrated that DOX was loaded onto the ANPs at high loading and encapsulation efficiency (11.96 and 99.68%, respectively).The drug release study indicated that ANPs can be used as a pH sensitive drug delivery system. In the second part of the study, ANPs showed good biocompatibility according to the MTT assay. Additionally, cellular uptake study revealed the ability of ANPs to deliver DOX into the cells through endocytosis. In addition, the antitumor effect of DOX-ANPs was tested by TEM, SEM, MTT assay and flow cytometric analysis. These results indicated that DOX-ANPs induced G2/M arrested, and showed an efficient cytotoxicity against OS cells, close to the toxicity effect of DOX. In the third part of the study,the single dose toxicity study of ANPs in vivoshowed the maximum tolerated dose was 180 mg/kg. In the repeated dose toxicity study of ANPs (14 days), there was no sign of toxicity or mortality at the low dose (30 mg/kg). The toxicity study indicated that ANPs (below 30 mg/kg) at the low dose (30 mg/kg). The toxicity study indicated that ANPs (below 30 mg/kg) showed potential as drug carrier without acute toxic side effect. In the last part of the study,the DOX-ANPs treatment groups (2 mg and 1.5 mg DOX/kg) can significantly reduce the tumor volume and increase the surviving ratio (p< 0.05), compared to the OS model group. In addition, these two DOX-ANPs groups showed less toxicity to the normal organs (p< 0.05), compared to the free DOX group.Taken together, these results highlight the promising application of ANPs derived from cockle shells as an effective drug delivery system for a successful chemotherapy against OS.